Kualitas Pelayanan Publik Yang Ada di Kota Batam - M. Aidil Zulfa; Paris Likuwatan (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
Research on public services in Batam City has been carried out with various focuses and approaches. Research conducted at the Batam City Public Service Mall aims to analyze the level of satisfaction with public services with changes to the business licensing regulatory system. The research results show that the majority of people express satisfaction with the services provided by the Batam City Public Service Mall, however there are improvements that need to be made, especially regarding understanding the procedures for processing business permits. Apart from that, other research highlights the influence of service quality and facilities on Batam City Government customer satisfaction at Public Service Malls. The results of this research provide an understanding of the importance of service quality and facilities in influencing customer satisfaction Apart from that, the implementation of public services during the Covid-19 pandemic in Batam City is also the focus of research. This research highlights the challenges in running public services according to the minimum standards that apply during the pandemic. The research results show that the implementation of public services during the Covid-19 pandemic is still not running effectively and efficiently From these various studies, it can be concluded that public services in Batam City are an important topic to evaluate and improve, especially in terms of customer satisfaction, the influence of service quality and facilities, as well as challenges in providing public services during pandemic conditions.